Предмет: Математика,
автор: bairangulova2
y+3 3y-7 9-y
----- + ------ - ------ = 1
2 3 6
Ответ запиши десятичной дробью
Ответы
Автор ответа:
0
( y + 3 ) / 2 + ( 3y - 7 ) / 3 - ( 9 - y ) / 6 = 1
общий знаменатель 6
3( y + 3 ) + 2( 3y - 7 ) - ( 9 - y ) = 6
3y + 9 + 6y - 14 - 9 + y = 6
10y = 6 + 14
y = 20 : 10
y = 2
общий знаменатель 6
3( y + 3 ) + 2( 3y - 7 ) - ( 9 - y ) = 6
3y + 9 + 6y - 14 - 9 + y = 6
10y = 6 + 14
y = 20 : 10
y = 2
Похожие вопросы
Предмет: Математика,
автор: shuichipidr
Предмет: Математика,
автор: smokker711
Предмет: Геометрия,
автор: kotletka73
Предмет: Физика,
автор: ВашаГеймерша